Long‐term outcomes following fractional flow reserve‐guided treatment of angiographically ambiguous left main coronary artery disease: A meta‐analysis of prospective cohort studies. Issue 1 (19th March 2015) - Mallidi, Jaya; Atreya, Auras R.; Cook, James; Garb, Jane; Jeremias, Allen; Klein, Lloyd W.; Lotfi, Amir
<x xml:space="preserve">Abstract</x> Objective To define the long term outcomes of Fractional Flow Reserve (FFR) guided revascularization of ambiguous left main coronary artery (LMCA) lesions by performing a pooled meta‐analysis of all available studies. Background Prospective studies evaluating the use of fractional flow reserve (FFR) for clinical decision‐making in ambiguous unprotected left main coronary artery (LMCA) stenosis suggest the relative safety of that approach, but any final conclusions are limited by small sample size. We performed a pooled meta‐analysis of studies to define the long‐term outcomes in these patients. Methods Six prospective cohort studies involving 525 patients met the inclusion criteria. Patients underwent revascularization (revascularization group) or medical therapy (deferred group) based on FFR. The primary outcome was defined as rate of major cardiovascular events (a composite of death from all causes, nonfatal myocardial infarctions and subsequent revascularizations). The secondary outcomes included individual components of the primary end point. Pooled effect sizes were calculated using a fixed effects model. Results Based on the FFR results, 217 patients (41%) underwent revascularization. There was no statistically significant difference between the groups in the rates of primary end point (P = 0.15), all‐cause mortality (P = 0.06) or nonfatal myocardial infarctions (P = 0.76). However, there was a significant increase in the rate of subsequent revascularizations in the deferred patients (P = 0.002). Conclusion The long term clinical outcomes in patients with ambiguous LMCA stenosis for whom revascularization is deferred based on FFR are favorable and similar to the revascularized group in terms of overall mortality and subsequent myocardial infarctions. © 2015 Wiley Periodicals, Inc.